Sistem Informasi Pembayaran Berbasis Web Pada Rumah Makan Padang Sederhana Minang Dengan Metode Scrum - Reynaldi Nugraha Riztanto; Syahbaniar Rofiah (Journal of Students‘ Research in Computer Science, 2024)
Technology increasingly advanced and developing rapidly, on the other hand technology plays a very important role at this time, especially in the field of entrepreneurship. Minang Simple Padang Restaurant currently does not yet have restaurant information media that can integrate restaurant business processes. In terms of providing restaurant information, so far it tends to be slow, the business process of payment and restaurant financial reporting is not going well. Overcoming the above problems requires a payment information system that can change the concept of payment, financial reports, and data storage in an effective and efficient manner, especially restaurant payment information systems that are centered on restaurant staff. This study uses the scrum model as a software development model. Payments made are integrated with Midtrans, the programming language used is PHP and uses the codeigniter framework that supports MCV (model, view, and controller), and the database uses MySQL. With this website, it makes it easier for customers to make cash and non-cash payments using QRIS.